Ubicación óptima de generación distribuida en sistemas eléctricos de distribución basado en costos de operación - Ayala Maldonado, Dukeyro Eduardo (2017)
The paper present the mathematical model that allows determining optimally the location and size of distributed generation in a distribution network, both technically and economically, using the General Algebraic Modeling System (GAMS) optimizer. The methodology initially considers the simulation of power flows of the radial topology distribution system of 33 buses, generic of the IEEE, next propose a mathematical model solved through mixed nonlinear integer programming using the optimizer GAMS, The objective function is the operational system costs minimization, without the initial investment, but respect the restriction of the power flow system. The model results, obtain the location of DG to be inserted in the system. Finally, the impact of this, in voltage profile, active power limits of the distribution lines, generate demands scenarios with annual growing for 5 years, to probe the sensibility of model on demand changes.